Anxiety and Functional Disability in a Large Sample of Children and Adolescents with Chronic Pain - Laura E Simons; Christine B Sieberg; Robyn Lewis Claar (Pain Research and Management)
BACKGROUND: Anxiety is the most common psychiatric condition in children and adolescents, and is linked to significant disruptions across domains of function. Due to the avoidant nature of anxiety and pain-related disability, studying anxiety symptoms in children with chronic and recurrent pain conditions is important.